Demographic Drivers of Environmental Pollution Perception in Nigeria: A Quantitative Analysis - Moshood Babatunde Lawal (Scientia Publica Media, 2026)
This study investigates how demographic and geographical factors influence people’s perceptions of pollution in Nigeria, utilising data from Afrobarometer Round 9. It focuses on demographic variables such as age, education level, and gender, alongside geographic factors, including residence in rural versus urban areas and differences among Nigerian regions. The research employs both descriptive and inferential statistical methods, like independent t-tests, analysis of variance (ANOVA), and Pearson’s correlation, to uncover patterns and relationships in pollution perception. The analysis reveals significant variations in how pollution is perceived across the different regions in Nigeria (F(5, 1599) = 26.676; p < 0.01), with distinct regional disparities but no statistically meaningful differences related to age. Particularly, individuals living in urban areas and those residing in the Northeast and Southeast regions of the country show heightened concern about pollution. Gender also plays a role, with males demonstrating a slightly higher level of awareness regarding pollution, supported by a small but significant positive correlation (r = 0.058, p < 0.001). Similarly, education positively correlates with pollution concern (r = 0.051, p < 0.001), indicating that higher educational attainment is linked with greater environmental awareness. Among specific environmental concerns, sanitation issues and plastic waste pollution stand out as the most urgent problems, cited by roughly a quarter of respondents. These insights suggest the importance of regional and demographic tailoring of public policies and environmental awareness campaigns. The study underscores the need for strategically designed interventions that cater to community-specific issues and demographics to improve pollution management and foster sustainable environmental practices across Nigeria.